Global Proving of Natural Silver - Shukla, Chetna; van der Zee, Harry (Homœopathic Links, 2014)
In 2005, a project was started called Global Proving which involved three substances, Himalayan Crystal Salt, Natural Silver and Arizona Clay. The idea of using a proving not only to get to know the substance but also and primarily to bring about a change in the collective is new in homeopathy and this global proving was a first experiment. Similar to what Hahnemann already stated that participating in provings has positive effects for the prover we may assume that the participation of larger numbers of people in a proving may have positive effects on the collective. The results of the second substance, Natural Silver, are discussed in this article.
Keywords: Proving; Global proving; Natural silver; Argentum metallicum; Moon; Time; Mistakes; Heart; Central nervous system; Nerves; Neuralgia; Electricity; Masculine/Male energy; Lesbian relationships; Money; Power; Mind; Body; Anxiety; Nervous; Anticipation; Control; Boundaries; Expansion; Big; Huge; Number 2; Silver; Pregnancy; Fertility; Mirrors